Osteocalcin serum concentrations and markers of energetic metabolism in pediatric patients. Systematic review and metanalysis - Rodríguez-Narciso, Silvia; Martínez-Portilla, Raigam Jafet; Guzmán-Guzmán, Iris Paola; Careaga-Cárdenas, Gabriela; Rubio-Navarro, Brenda Jazmin; Barba-Gallardo, Luis Fernando; Delgadillo-Castañeda, Rodolfo; Villafan-Bernal, José Rafael (Frontiers in Pediatrics, 2023)
Background: Osteocalcin plays a role in glucose metabolism in mice, but its relevance in human energetic metabolism is controversial. Its relationship with markers of energetic metabolism in the pediatric population has not been systematically addressed in infants and adolescents. Objective: This study aims to assess the mean differences between tOC, ucOC, and cOC among healthy children and children with type 1 or type 2 diabetes (T1D or T2D) and the correlation of these bone molecules with metabolic markers. Methods: A systematic review and metanalysis were performed following PRISMA criteria to identify relevant observational studies published in English and Spanish using PubMed, Scopus, EBSCO, and Web of Science databases. The risk of bias was assessed using New Castle–Ottawa scale. Effect size measures comprised standardized mean difference (SMD) and Pearson correlations. Heterogeneity and meta-regressions were performed. Results: The 20 studies included were of high quality and comprised 3000 pediatric patients who underwent tOC, cOC, or ucOC measurements. Among healthy subjects, there was a positive correlation of ucOC with WC and weight, a positive correlation of tOC with FPG, HDL-c, WC, height, and weight, and a negative correlation between tOC and HbA1c. Among diabetic subjects, a negative correlation of ucOC with HbA1c and glycemia in both T1D and T2D was found and a negative correlation between tOC and HbA1c in T1D but not in T2D. The ucOC concentrations were lower in T2D, T1D, and patients with abnormal glucose status than among controls. The serum concentrations of tOC concentrations were lower among T1D than in controls. The patient's age, altitude, and HbA1c influenced the levels of serum tOC. Conclusion: Osteocalcin is involved in energy metabolism in pediatric subjects because it is consistently related to metabolic and anthropometric parameters.